FACTORS CONTRIBUTING TO POOR INVENTORY MANAGEMENT OF MEDICINES AMONG HEALTH WORKERS AT SOROTI REGIONAL REFERRAL HOSPITAL, SOROTI DISTRICT. A DESCRIPTIVE CROSS-SECTIONAL STUDY. - IVAN EMWOCHU; Amiri Were (Student's Journal of Health Research, 2023)
Background: The purpose of this study was to determine the factors contributing to poor inventory management of medicines among health workers in Soroti Regional Referral Hospital, Soroti District. The objectives were to determine the individual factors that contributed to poor inventory management of medicines and health facility-related factors that contributed to poor inventory management of medicines among health workers in Soroti regional referral hospital. Methodology: The study was a descriptive cross-sectional study. Data was collected from the respondents using a self-administered questionnaire and a purposive sampling technique was used. Results: Regarding individual factors, 6% of the respondents had not taken Integrated Pharmaceuticals Logistics System Training, Pre-service training, and job training like computer maintenance and HMIS, 6% of them had work experience below 3 years, 14% were not happy working in the pharmacy, 32% were not trained or oriented on EMLIP and 94% of the respondents had ever experienced stock-outs during their working experience. Based on the health facility-related factors, 32% of the respondents said drugs were dispensed from boxes from which they were supplied, 46% of the respondents did not dispense drugs by FIFO, FEFO, and LILO, 72% of the respondents did not arrange drugs in accordance to either ABC or according to pharmacological classes. Conclusion: Lack of training or orientation on EMLIP and working experience on stock-outs, poor dispensing according to FIFO, FRFO, and LILO, and arrangement of drugs by ABC and pharmacological classes were the factors contributing to poor inventory management. Recommendation: The researcher recommended that the government of Uganda through the Ministry of Health should come up with absolute resolutions to combat these problems efficiently and effectively to ensure better and proper methods of inventory management of medicines to improve the welfare of patients' health-wise.